A Phase I/II Study of the Investigational Drug Alisertib in Combination With Abiraterone and Prednisone for Patients With Metastatic Castration-Resistant Prostate Cancer Progressing on Abiraterone. (24th October 2016) - Lin, Jianqing; Patel, Sheel A.; Sama, Ashwin R.; Hoffman-Censits, Jean H.; Kennedy, Brooke; Kilpatrick, Deborah; Ye, Zhong; Yang, Hushan; Mu, Zhaomei; Leiby, Benjamin; Lewis, Nancy; Cristofanilli, Massimo; et al.
Abstract : Lessons Learned : Patients with metastatic castration-resistant prostate cancer did not tolerate the combination of alisertib with abiraterone and prednisone. There was no clear signal indicating that adding alisertib might be beneficial for those patients progressing on abiraterone. Background: We hypothesized that Aurora A kinase (AK) contributes to castrate resistance in prostate cancer (PCa) and that inhibiting AK with alisertib can resensitize PCa cells to androgen receptor (AR) inhibitor abiraterone. Methods: This was a phase I/II trial to determine the safety and efficacy of alisertib when given in combination with abiraterone plus prednisone (AP). Metastatic castration-resistant prostate cancer (mCRPC) patients were treated with dose escalation (alisertib at 30, 40, and 50 mg orally b.i.d., days 1–7 every 21 days) per standard 3+3 design. Results: Nine of 43 planned subjects were enrolled. The maximum tolerated dose (MTD) was not reached, and the dose-limiting toxicities (DLTs) included neutropenic fever (1 of 9), neutropenia (1 of 9), fatigue with memory impairment (1 of 9), and diarrhea/mucositis (1 of 9). No prostate-specific antigen (PSA) decrease or circulating tumor cell (CTC) changes were observed during the study. Pharmacodynamically, adding alisertib did not affect total testosterone or dehydroepiandrosterone (DHEA) levels. There was some change in neuroendocrine markers after therapy. Mean duration on study was 2.5 months. The trial was terminated early. Conclusion: A tolerable dose of alisertib in combination with AP in mCRPC was not established in this study. There was no clear signal indicating that alisertib might be beneficial for patients with mCRPC progressing on abiraterone.